PENGINGKARAN JANJI OLEH PENJUAL TERHADAP JUAL BELI SEBAGIAN TANAH WARISAN YANG DIBUAT DENGAN AKTA DIBAWAH TANGAN (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 1944 K/Pdt/2011) - Z U L F I A N I Z U L F I A N I (PREMISE LAW JURNAL, 2016)
Buying and selling on certified land with underhanded certificate as I is siplated in he Ruling of the Supereme Court No 1944K/Pdt/2011 which caused land dispute. It waBuying and selling on certified land with underhanded certificatewhich causedland dispute.It was because the process of settling and transfer title of the certificate was rejected by the National Land Board made underhandedly.It was diffrent in Article 37, paragraph 1 of the Government Regulation No. 24/1997. The plaintiff (the Buyer) asked the Defendant (the Seller) to resign the Purchase Certificate, but the Defendant refused because there was no clausewhich required the Seller and the Buyer to sign it before PPAT. The Buyer (Plaintiff) who was harmed filed a complaint to the Court about the underhanded Purchase Certificate as the evidence of legal act of buying and selling of the part of the land. Keywords: Default, Transfer Title, Certificate